Unpacking the impact of COVID-19 on child immunization: evidence from Ghana - Kathrin Durizzo; Koku Awoonor-Williams; Kenneth Harttgen; Isabel Günther (BMC, 2024)
Abstract Background With the onset of the COVID-19 pandemic, governments implemented social distancing regulations to limit the spread of the disease. Some health experts warned that these measures could negatively affect access to essential health services, such as routine childhood immunizations. Others noted that without these regulations, COVID-19 cases would increase, leading to overburdened health systems. Methods We analyze four years (2018-2021) of monthly administrative data on childhood immunizations in all administrative districts in Ghana and exploit variations in social distancing regulations across districts. Given variations in social distancing regulations across Ghanaian districts, we can further differentiate between the effect of public lockdowns and the effect of the pandemic. Results We find that child immunizations in Ghana declined by 6% during the public lockdown in April 2020, but the country compensated with higher vaccination rates starting in June, and immunization services recovered to pre-pandemic growth levels by 2021. Time-critical vaccines, such as polio, were not affected at all. We do find a substantially larger disruption in April 2020 (14%) and a slower recovery in 2020 in the 40 lockdown-affected districts. Interestingly, vaccination rates already decreased in February and March by about 5% before the public lockdown and before the pandemic had reached Ghana, but with the pandemic already spreading globally and in the news. Conclusion Our results indicate that the negative effect on child immunization was less severe and shorter than predicted by experts. Fear of COVID-19 and delayed vaccination campaigns had a substantial impact on childhood immunization while rising COVID-19 cases and moderate social distancing regulations did not seem to affect immunization rates.